PENGEMBANGAN MEDIA KOMIK BERBASIS SOCIO SCIENTIFIC ISSUE (SSI) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Purwanto, Sigit; Trisnayanti, Yetty; Lontoh, Willy; Miterianifa; Suryani , Novi Ade (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Integrated Natural and Social Sciences (IPAS) learning in elementary schools requires media that can contextually combine scientific and social concepts, yet observations at SD Negeri 2 Sidoharjo revealed that fifth-grade students reading interest remained low due to limited engaging materials and the absence of a socio-scientific issue-based medium capable of raising students awareness of environmental problems, particularly in the unit Bumiku Sayang, Bumiku Malang. This study aimed to develop a comic medium based on socio-scientific issues and to examine its validity, practicality, and effectiveness in fifth-grade IPAS learning. The research employed a Research and Development method using the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. Try-out subjects comprised three expert validators covering language, media, and content, three students in the one-to-one trial, six students in the small-group trial, and 26 students together with one class teacher in the large-group trial. Data were collected through validation questionnaires, practicality questionnaires, and learning outcome tests, then analyzed using Aiken's V formula for validity, percentage scores for practicality, and classical mastery for effectiveness. Results showed the comic medium was valid, with an average Aiken's V of 0.90 in the high category, comprising 0.96 for language, 0.84 for media, and 0.91 for content validation. The practicality test obtained an average percentage of 89.55 percent, categorized as very practical, while the effectiveness test showed a classical mastery of 89.23 percent, with 24 of 26 students meeting the mastery criteria, categorized as highly effective. Therefore, the comic medium is feasible for use as IPAS learning media to foster reading interest and raise fifth-grade students awareness of environmental issues around them